Wom(b)an : a cultural-narrative reading of the Hebrew Bible barrenness narratives - De-Whyte, Janice Pearl Ewurama. (Biblical Interpretation Series, 2018)
In Wom(b)an: A Cultural-Narrative Reading of the Hebrew Bible Barrenness Narratives Janice Pearl Ewurama De-Whyte offers a reading of the Hebrew Bible barrenness narratives. The original word "wom(b)an" visually underscores the centrality of a productive womb to female identity in the ANE and Hebrew contexts. Conversely, barrenness was the ultimate tragedy and shame of a woman. Utilizing Akan cultural custom as a lens through which to read the Hebrew barrenness tradition, De-Whyte uncovers another kind of barrenness within these narratives. Her term "social barrenness" depicts the various situations of childlessness that are generally unrecognized in western cultures due to the western biomedical definitions of infertility. Whether biological or social, barrenness was perceived to be the greatest threat to a woman's identity and security as well as the continuity of the lineage. Wom(b)an examines these narratives in light of the cultural meanings of barrenness within traditional cultures, ancient and present.